2021
DOI: 10.3390/ijms22147264
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Microparticles Decrease Daunorubicin-Induced DNA Damage and Modulate Intrinsic Apoptosis in THP-1 Cells

Abstract: Platelets can modulate cancer through budding of platelet microparticles (PMPs) that can transfer a plethora of bioactive molecules to cancer cells upon internalization. In acute myelogenous leukemia (AML) this can induce chemoresistance, partially through a decrease in cell activity. Here we investigated if the internalization of PMPs protected the monocytic AML cell line, THP-1, from apoptosis by decreasing the initial cellular damage inflicted by treatment with daunorubicin, or via direct modulation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…A growing body of evidence suggests that PEVs are also important regulators of cancer progression and modulate key steps of the metastatic cascade [4,5]. Speci cally, PEVs display the remarkable ability to bind tumor cells and to regulate their survival and intrinsic aggressiveness [6][7][8][9][10][11]. In previous studies, we have characterized the mechanism of platelet activation induced by breast cancer cells [12], and we have demonstrated that breast cancer cells can also induce the release of PEVs [7].…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence suggests that PEVs are also important regulators of cancer progression and modulate key steps of the metastatic cascade [4,5]. Speci cally, PEVs display the remarkable ability to bind tumor cells and to regulate their survival and intrinsic aggressiveness [6][7][8][9][10][11]. In previous studies, we have characterized the mechanism of platelet activation induced by breast cancer cells [12], and we have demonstrated that breast cancer cells can also induce the release of PEVs [7].…”
Section: Introductionmentioning
confidence: 99%